Monitoring dan Evaluasi IKM Tekstil dan Produk Tekstil di Kota Bandung - Wahyuniardi, Rizki; Fathoni, Riza; Nurjaman, Sidik; Gusdya, Wanda (Universitas Katolik Parahyangan, 2017)
Small and Medium Enterprise (SME) as a part of the national industrial sector has a critical influence in developing economic, social and political state of Indonesia. Therefore, the government has issued many policies, programs, and activities to enhance the development of SMEs. The absence of an online information system that shows the development of the SME cause the government has difficulty in overseeing the development of SMEs. Difficulties experienced by the government due to lack of information also in line with Law No. 3 of 2014 on Industry, precisely on Article 64 which stated that the industry is obligated to submit industry data that are accurate, complete, and timely periodically to the Minister, governors and regents/mayors. Therefore, the industry, in particular Small and Medium Enterprise (SME), requires a web-based information system that will be a tool that can be used by industry to facilitate the reporting of industrial activities. Therefore, this research aimed to develop a web- based information system for SMEs Sentra Textiles and textile products (TPT) in West Java. The system will contain information about the condition and position of SMEs Sentra Textiles and textile products (TPT) in Bandung, West Java. In addition to preparing an information system, this research will conduct an analysis of the current condition of SMEs to be taken into consideration in making the SME development strategy.Keywords: evaluation, monitoring, center, information systemsÂ